Nuclear reactor materials at the atomic scale - Marquis, E.; Hyde, J.; Saxey, David; Lozano-Perez, S.; de Castro, V.; Hudson, D.; Williams, C.; Humphry-Baker, S.; Smith, G. (2009)
With the renewed interest in nuclear energy, developing new materials able to respond to the stringent requirements of the next-generation fission and future fusion reactors has become a priority. An efficient search for such materials requires detailed knowledge of material behaviour under irradiation, high temperatures and corrosive environments. Minimizing the rates of materials degradation will be possible only if the mechanisms by which it occurs are understood. Atomic-scale experimental probing as well as modelling can provide some answers and help predict in-service behaviour. This article illustrates how this approach has already improved our understanding of precipitation under irradiation, corrosion behaviour, and stress corrosion cracking. It is also now beginning to provide guidance for the development of new alloys. © 2009 Elsevier Ltd. All rights reserved.